Economic evaluation of animal traction - a comparative analysis of hoe and bullock farming systems in northern Ghana - Panin, A.; Haen, H. de (1989)
Presents the results of a comparative analysis of the hoe and bullock farming system conducted in the households of three villages of Ghana. Examines impacts of bullock traction technology on size of cultivated area, cropping patterns, mixed cropping systems, crop yields, labour use and input, household income and delays in learning through experience.